A Trojan horse: anti-communism and the war on drugs - Bullington, Bruce (Contemporary crises, 1990)
This work argues the U.S. "War on Drugs" is a misnomer. We suggest, instead, that it is secondary to traditional anti-Communist foreign policy concerns. Thus, "the war on drugs" serves to mask the U.S. counter-intelligence and paramilitary presence abroad.